Realisasi Pendidikan Multikultural di Pesantren - Refriana, Isna; Rizal, Imam; Asiyah, Asiyah (JOEAI (Journal of Education and Instruction), 2022)
This study aims to find out and understand how the implementation of multicultural education at the Izzul Qur'an Islamic Boarding School in Pagar Alam City, South Sumatra. The type of research used is field research (field research). The research approach is using a qualitative approach. Furthermore, the data collection methods carried out are observation, interviews and documentation. Data analysis techniques by means of data reduction, data presentation, and conclusions. The results obtained indicate that the Izzul Qur'an Islamic Boarding School has instilled the values ​​of multicultural education, which can be seen from various sides including educators, students and activities in the Izzul Qur'an Islamic boarding school. In conclusion, multicultural education at the Izzul Qur'an Islamic boarding school in Pagar Alam City has been well realized, as can be seen from the various educators, students, and learning processes that interact, respect and respect each other. Keywords: Education, Multicultural, Islamic Boarding School